Knowledge, Attitudes, and Practices of Nurses towards Oral Care of Hospitalized Patients in Zimbabwe - Fiona Makoni; Cleopatra Matanhire-Zihanzu; Timothy Chifamba; Lilian Gertrude Dodzo; Mordester Mutimukulu (Adventist University of Africa, 2022)
Background: This study aimed to evaluate oral healthcare knowledge, attitudes, and management of admitted patients by Registered General Nurses (RGNs). It sought to appreciate the scope of training in the oral health management of patients using RGNs and the knowledge, attitudes, and practices of RGNs in managing oral and maxillofacial conditions in admitted patients. Method: This descriptive cross-sectional study used systematic random sampling to collect data using questionnaires at Parirenyatwa Hospital, Harare. One hundred and one RGNs participated in this study. Results: The overall knowledge level of RGNs regarding oral and maxillofacial management of admitted patients was average. In addition, their general attitude regarding the oral and maxillofacial management of admitted patients was good, but their overall practice was considered fair. Conclusion: These results show a disparity, with generally lower practices than self-perceived attitudes. Nurses should be equipped with a basic package of oral care for admitted patients through collaboration between oral health professionals and nursing professionals in research, training, and service.